Anesthesia Management in VP Shunt Surgery in Neonates with Hypoplastic Left Heart Syndrome (HLHS) and Dandy Walker Syndrome - Purwoko Purwoko; Fandi Ahmad Muttaqin (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2021)
Introduction: Hypoplastic left heart syndrome (HLHS) is defined as the incomplete development of the left heart structures, including the mitral valve, left ventricle, aortic valve, and aortic arch. The clinical presentation of HLHS depends on the patency of the ductus arteriosus and the degree of restriction of the atrial septum. Common clinical manifestations include cyanosis, respiratory distress, and hemodynamic instability within hours of delivery. Delays in diagnosis and delay in intervention will increase the morbidity of neonates with HLHS.Purpose: To understand the mechanism of HLHS along with the principles of anesthesia in neuroaesthetics procedures in pediatrics in order to obtain a good outcome.Case Illustration: A 9-day old baby girl, weight 2522 grams with HLHS (aortic atresia) with patent ductus arteriosus (PDA), type II atrial septal defect (ASD) with a left to right shunt, and dandy walker syndrome. From the physical examination, the patient's condition is stable, with GCS E4V5M6, pulse 130-135 beats/minute, breath rate 48x / minute, and SpO2 94-98%. The patient's head was enlarged from birth, no heart sounds were found, regular I-II heart sounds. Blood laboratory tests showed a total bilirubin value of 11.7 mg / dL, direct bilirubin 0.64 mg / dL, indirect bilirubin 10.43 mg / dL, hemoglobin 20.1 g%, hematocrit 55%, with leukocytes 19.9x103 / L, platelets 216 x 103 / L, serum Na 122 mmol / L, K 7.8 mmol / L, Cl 101 mmol / L.Discussion: The anesthetic approach in HLHS is to maintain preoperative hemodynamic stability by maintaining heart rate, preload, and PGE1, balancing systemic vascular resistance and pulmonary vascular resistance, preventing too high PaO2, and administering inotropic agents to increase cardiac output and keep the patent ductus arteriosus open. The balance of systemic and pulmonary blood flow is a key principle in the management of HLHS anesthesia. Conclusion: The main goal of HLHS anesthesia is to minimize hemodynamic changes to prevent compromised hemodynamics in both circulations and maintaining stability is essential in preventing morbidity, complications, and increasing good outcomes in surgery..